Piecing together the puzzle: Mobility as a Service from the user and service design perspectives - Jana Sochor (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
Many regions are seeking to improve mobility choices for citizens, both in congested city settings and poorly connected peripheral communities. Mobility as a Service (MaaS) is increasingly presented as a possible solution, yet beyond pilot level there are no examples to date of what a successful implementation of MaaS might look like. This paper reviews pilot studies and ongoing research into the user perspective on MaaS and the lessons learned thus far.
Keywords: 330